BIMBINGAN DAN PENGARAHAN DIVERSIFIKASI PRODUK SEBAGAI UPAYA MENINGKATKAN OMZET USAHA KECIL - Joni Dwi Pribadi; Rena Feri Wijayanti; Siti Rohani; Kun Mustain; Sugeng Hariyanto (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Business activities always face various challenges in the competition to continue to survive. Several strategies were developed to answer the challenges faced. Entrepreneurs as a business mover both small and medium-scale businesses to large-scale businesses cannot avoid continuing to make breakthrough strategies in order to achieve the success of their businesses. The small business sector where there are still many limitations requires a lot of help and motivation to be able to take advantage of every opportunity and also the available resources. From this aspect it can be understood that the world of education can make a real contribution to fostering businesses that can still be developed according to their potential.